Management of surgical wounds considering the type, technique and supplies used in an a health providing institution." Armenia, Quindío, 2014 (Revista de Investigaciones Universidad del Quindío, 2017)
This article is about the procedures and results of the research "Manejo de las heridas quirúrgicas, desde el tipo, técnica e insumos utilizados en una ips. Armenia, Quindío, 2014. Its main purpose was to describe the methods managed by nursing staff for wound care in the procedures, in order to know in detail the techniques and processes used in the procedure (materials, steps, sepsis, etc.), contrasting these with scientific and technological advances in this field and at last determine nursing care provided to hospitalized adult patients with wounds of different etiology. The research was transversal descriptive and the sample was obtained through purposive sampling; surgical wound of hospitalized patients in surgical departments, admitted during a trimester by elective surgery, surgical  complications or emergency surgery, in a third level hospital of care. The people studied had the opportunity to voluntarily choose their participation. The technique for data collection was video recording the proceedings; subsequently the guide for supplementary information was filled, the data was carried out to a Databases built and processed in SPSS. Results: 51 patients were analyzed: 29 from general surgery, 3 from neurosurgery, 11 from orthopedics, 2 from plastic surgery , 4 from internal medicine, and 2 from urology. Findings: The handling of the wound continues being traditional with products provided by the institution such as gauze, dressings, saline, Furacin and alcohol. However, there are products that contribute to effective healing care of the wound or debridement. These are seldom used, and the use of polyvinyl in open wounds was evident. The techniques were found inadequate; the procedure is not done in a systematic way (auxiliary or professional staff). There documentation process is not efficient, privacy aspects and comfort (secondary) are not taken into account, the educational approach patient / family is irrelevant. Recommendations: Resume leadership from the professional nurses, management in care of the person injured. This would result in the identification and institutional availability of equipment, supplies and care items. Resume the rigorous biosecurity update protocols and ensure staff adherence to wound care according to scientific advance, sensitize all health team around humanized care, develop processes in institutional tracking and monitoring to ensure infection control; and structure processes of induction and re-induction to staff.
Keywords: Care; Healing; Nursing; Wounds; Human Beings